Ampullary duodenal diverticulum and cholangitis - Castilho Netto, Joaquim Mendes; Speranzini, Manlio Basilio (São Paulo Medical Journal, 2003)
CONTEXT: Ampullary duodenal diverticulum complicated by cholangitis is little known in clinical practice, especially when there are no gallstones in the common bile duct or there is no biliary tree ectasia or hyperamylasemia. A case of this association is presented, in which the surgical treatment was a biliary-enteric bypass. CASE REPORT: A 74-year-old diabetic white woman was admitted to the Taubaté University Hospital, complaining of pain in the right upper quadrant, jaundice and fever with chills (Charcot’s triad). She had had cholecystectomy 30 years earlier. She underwent clinical treatment with parenteral hydration, insulin, antibiotics and symptomatic drugs. Imaging examinations were provided for diagnosis: ultrasound, computed tomography and endoscopic retrograde cholangiopancreatography. The surgical treatment consisted of choledochojejunostomy utilizing a Roux-en-y loop. The postoperative period progressed without incidents, and a DISIDA scan demonstrated the presence of dynamic biliary excretion. The patient remained asymptomatic when seen at outpatient follow-up.